2016
DOI: 10.1007/s10544-016-0047-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of reference point indentation for micro-mechanical surface characterization of calcium silicate based dental materials

Abstract: The objective of this study was to elucidate micromechanical properties of Biodentine and two experimental calcium silicate cements (CSCs) using Reference Point Indentation (RPI). Biomechanical characteristics of the cement type and the effects of a radiopacifier, liquid components, acid etching treatment and bioactivation in simulated body fluid (SBF) were investigated by measuring the microhardness, average unloading slope (Avg US) and indentation distance increase (IDI). Biodentine had a greater microhardne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
2
1
Order By: Relevance
“…Only one previous study evaluated the microhardness of Biodentine, but the study examined only the effects of EDTA and acids on the microhardness of the material. 12 The study found that physical properties of Biodentine were weaker after EDTA treatment, which was in contrast to the findings in the present study. The discord between our results and those of the previous study may be related to differences in test methods (Vickers microhardness test versus reference point indentation).…”
Section: Discussioncontrasting
confidence: 99%
“…Only one previous study evaluated the microhardness of Biodentine, but the study examined only the effects of EDTA and acids on the microhardness of the material. 12 The study found that physical properties of Biodentine were weaker after EDTA treatment, which was in contrast to the findings in the present study. The discord between our results and those of the previous study may be related to differences in test methods (Vickers microhardness test versus reference point indentation).…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to the present study, Antonijević et al . [ 17 ] showed that the microhardness of Biodentine was reduced after being treated with 17% EDTA. This is because 17% EDTA has a strong chelating impact, which normally affects the microhardness of Biodentine over an extended period which is also supported by Wang et al .,[ 18 ] who reported that solutions with acidic pH such as EDTA weaken the microhardness of MTA.…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed significant difference in microhardness and indentation values between pure CS cements, which demonstrated better features and radio pacified cements. Micromechanical properties were not affected by using different liquid components [64]. When adding different radiopacifiers to CS cements, engineers should be careful having in mind that some radiopaque agents (BaSO4 and CHI3) result in different radiopacities of the final mixture on dental film and digital sensor [65].…”
Section: Physico-chemical Properties Of Cs Cementsmentioning
confidence: 99%